BS IEC 61156-15. Multicore and symmetrical pair/quad cables for digital communications. Part 15. Symmetrical pair/quad cables for horizontal floor wiring with transmission characteristics up to 1 000 MHz and resistance to fire performance characteristics. Sectional specification (13th January 2022) - British Standards Institution
No abstract available